Peranan Modal Ventura Syariah dalam Meningkatkan UMKM di Indonesia - Niken Ning Tiyas; Muhammad Zidan Maulana; Etika Alina Putri; Laeni Khazimah; Marfita Hikmatul Aini; Muhammad Taufiq Abadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to understand the role of sharia venture capital, using a qualitative approach by utilizing in-depth analysis of secondary data from various related literature sources. The data collection technique used is a literature study technique to obtain a theoretical basis in the form of opinions or writings of legal experts, ulama and other authorities regarding the role of sharia venture capital in Indonesia. This research is descriptive in nature to analyze research results but is not used to draw broader conclusions. The results of this research conclude that Indonesia, as a country whose economy continues to grow, faces major challenges in increasing the competitiveness of the micro, small and medium enterprise (MSME) sector. Participate in Direct Equity Company capital participation (PMV) to the partner company by taking a certain number of shares in the Partner Business Company (PPU). In carrying out venture capital financing, it starts with a venture agreement in each implementation, but don't forget to include the provisions of Islamic law in accordance with the best Sharia Venture Capital Companies (PMVS).Keywords: venture capital, capital financing, micro, small and medium enterprise sector